Study of Photoluminescence Properties of CuxO Thin Films Prepared by Reactive Radio Frequency Magnetron Sputtering. Issue 1792 (11th June 2015) - Gan, Jiantuo; Galeckas, Augustinas; Venkatachalapathy, Vishnukanthan; Riise, Heine N.; Svensson, Bengt G.; Monakhov, Edouard V.
ABSTRACT: Cux O thin films have been deposited on a quartz substrate by reactive radio frequency (rf) magnetron sputtering at different target powers Pt (140-190 W) while keeping other growth process parameters fixed. Room-temperature photoluminescence (PL) measurements indicate considerable improvement of crystallinity for the films deposited at Pt >170 W, with most pronounced excitonic features being observed in the film grown using Pt =190 W. These results corroborate well with the surface morphology of the films, which was found more flat, smooth and homogeneous for Pt >170 W films in comparison with those deposited at lower powers.